Asymptomatic neurocognitive impairment is a risk for symptomatic decline over a 3-year study period. (1st January 2021) - Rourke, Sean B.; Bekele, Tsegaye; Rachlis, Anita; Kovacs, Colin; Brunetta, Jason; Gill, M. John; Carvalhal, Adriana; Cysique, Lucette A.; Marcotte, Thomas; Power, Christopher
Abstract : Objective: To examine whether persons with asymptomatic neurocognitive impairment (ANI) were more likely to show progression to mild neurocognitive disorder or HIV-associated dementia than those who were neuropsychologically normal (NP-N). Design: Longitudinal observational cohort study. Methods: Study sample included 720 HIV-1 seropositive persons (317 with ANI and 403 NP-N) receiving care in Toronto, Canada [83% were on antiretroviral treatment; 71% had undetectable (<50 copies/ml) plasma HIVRNA]. Neuropsychological assessments were conducted at 12 months intervals for a median follow-up time of 34 months. Neuropsychological data were corrected for age, education, sex, and race/ethnicity, and corrected for practice effect at follow-ups. Progression to mild neurocognitive disorder and HIV-associated dementia at each time point was determined using the Global Deficit Score and presence of cognitive symptoms. Results: Over the follow-up period, 170 individuals (24%) progressed to symptomatic HIV-associated neurocognitive disorders (HAND). Persons with ANI were more likely to progress to symptomatic HAND than persons with NP-N after adjusting for baseline and time-varying confounders (adjusted hazards ratio: 1.88; 95% confidence interval: 1.37–2.60; P   <  0.001). Female sex, depression, and cigarette smoking were associated with higher risk of progression to symptomatic HAND, but traditional HIV markers and antiretroviral treatment were not. Conclusion: ANI is associated with a two-fold increased risk of progression to symptomatic HAND in a cohort with universal healthcare access. This represents the largest replication of comparable US results. Reproducibility of these findings indicate that routine monitoring of persons with ANI and exploration of clinical interventions to prevent or delay progression to symptomatic HAND are imperative. Search terms: HIV, HAND, HIV-associated dementia, cohort study, replicability, reproducibility.